Instilling Creative Spirit and Improving Work Ethics through Hypno Spiritual Teaching - Muhamad Sidik Afandi; Miftakhurozaq Miftakhurozaq; Muna Erawati (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
This study aims to instill spirit of creativity and improve the work ethic of students in applying the knowledge gained from learning related to renewal / creativity / innovation and enhancing the quality of students’ work. Thus, related to national education goals in Indonesia, there needs to be a lot of development in innovating learning in the classroom. The method used in this study is qualitative research, with a descriptive approach. The subjects of this study are 11th graders of Islamic Education Subject at Public Vocational High School (SMK N) 1 Tengaran, in the academic year of 2018. Data collection techniques uses observation, interviews and documentation. The data analysis technique is descriptive in analyzing the application of the content and the impact of the implementation of hypno spiritual teaching in learning Islamic Education (PAI) in shaping the character of renewal/creativity spirit and increasing work ethic of fashion students. As a result of the research, the value of learning spirit tobe a reformer in finding ideas/creations and enhancement of work ethics that can be found are: core competencies, syllabus-based competencies, and instructional books. The implementation of PAI in building the character of the spirit of creation and improvement of work ethic is manifested in the form of activities in learning, extracurricular activities, in daily life, and various habits in the school and learning methods used. The impact of PAI in shaping the character of the creativity/innovation spirit and improving the work ethic of students is the awareness of the importance of learning spirit as a reformer who is passionate in working to achieve a better future, and motivating other students to foster a spirit of learning/innovation and have a good work ethic.